2021
DOI: 10.1002/micr.30720
|View full text |Cite
|
Sign up to set email alerts
|

Three salvage strategies in microvascular fibula osteocutaneous flap for mandible reconstruction with vascular compromise and establishment of an algorithm

Abstract: Background Fibula osteocutaneous flap is associated with a higher rate of reexploration in mandible reconstruction due to limited space for the fixation of various tissue components on multiple segments of the fibula flap. To maintain optimal circulation to the flap and to prevent negative outcomes because of partial or total flap loss, we shared our experiences on salvaging the free fibula flap with vascular compromise in the first reexploration and we developed an algorithm. Methods From 1992 to 2018, 12 pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…The main advantage of this technique precisely lies in the anatomy of the bone itself, as a triangular-shaped bone which allows greater primary stability of the implants themselves, being a bicortical bone [25,26]. Moreover, one of the greatest strengths of the fibula free flap is that it can be manipulated without difficulty to fill defects on the inner and outer sides [27].…”
Section: Discussionmentioning
confidence: 99%
“…The main advantage of this technique precisely lies in the anatomy of the bone itself, as a triangular-shaped bone which allows greater primary stability of the implants themselves, being a bicortical bone [25,26]. Moreover, one of the greatest strengths of the fibula free flap is that it can be manipulated without difficulty to fill defects on the inner and outer sides [27].…”
Section: Discussionmentioning
confidence: 99%
“…If bony reconstruction is required, osteomyocutaneous fibula free flap, scapula flap, or deep circumflex iliac artery (DCIA) flap can be used. Depending on the type of flap, there is a flap survival rate of over 95% [ 1 , 2 , 3 , 4 , 5 ]. In addition to the type of MFF and the surgeon’s experience, several factors influencing the success rate of free tissue transfer have been identified.…”
Section: Introductionmentioning
confidence: 99%
“…6,7 On the other hand, microsurgery has its drawbacks: it is expensive, time-consuming, and requires high surgical skills, adequate instruments, and a trained team; moreover, a minimal possibility of a free flap failure is reported with all the problems related to a re-exploration and secondary reconstructive procedure. [8][9][10][11] To date, due to the wide spectrum of lower extremity defect presentations, no universal algorithm exists for their reconstruction; moreover, several studies showed no significant difference in terms of flap survival and complication rates between free and local flaps. 4,7,12 The introduction of angiosome and perforasome theories have allowed plastic surgeons to reevaluate the role of local flaps in light of the perforator concept.…”
Section: Introductionmentioning
confidence: 99%